C−I‐Selective Cross‐Coupling Enabled by a Cationic Palladium Trimer. Issue 1 (5th December 2018) - Diehl, Claudia J.; Scattolin, Thomas; Englert, Ulli; Schoenebeck, Franziska
Abstract: While there is a growing interest in harnessing synergistic effects of more than one metal in catalysis, relatively little is known beyond bimetallic systems. This report describes the straightforward access to an air‐stable Pd trimer and presents unambiguous reactivity data of its privileged capability to differentiate C−I over C−Br bonds in C−C bond formations (arylation and alkylation) of polyhalogenated arenes, which typical Pd 0 and Pd I ‐Pd I catalysts fail to deliver. Experimental and computational reactivity data, including the first location of a transition state for bond activation by the trimer, are presented, supporting direct trimer reactivity to be feasible. Abstract : An air‐stable cationic palladium trimer was employed in iodo‐selective arylations and alkylations of polyhalogenated arenes. Experimental and computational reactivity data, including the first location of a transition state for bond activation by the trimer, are presented, and support direct trimer reactivity to be feasible.